Winners : a novel - Steel, Danielle (Delacorte Press, 2013)
Paralyzed by a tragic chairlift accident, seventeen-year-old competitive skier Lily struggles with the loss of her Olympic dreams before meeting a young man, Teddy, who has overcome his own devastating injuries to pursue an enriching life.